Influence of Breed Size, Age, Fecal Quality, and Enteropathogen Shedding on Fecal Calprotectin and Immunoglobulin A Concentrations in Puppies During the Weaning Period. (8th June 2016) - Grellet, A.; Heilmann, R.M.; Polack, B.; Feugier, A.; Boucraut‐Baralon, C.; Grandjean, D.; Grützner, N.; Suchodolski, J. S.; Steiner, J.M.; Chastant‐Maillard, S.
Abstract : Background: Fecal calprotectin and immunoglobulin A (IgA) are markers of intestinal inflammation and immunity in adult dogs. Hypothesis: Fecal calprotectin and IgA concentrations in puppies are not influenced by fecal moisture in puppies but by enteropathogen shedding. Animals: Three hundred and twenty‐four puppies. Methods: Fecal consistency was assessed by gross examination. Fecal moisture was evaluated before and after lyophilization. Canine parvovirus and coronavirus were detected in feces by qPCR and qRT‐PCR respectively. Giardia intestinalis antigen was quantified by ELISA. The standard McMaster flotation technique was used to detect eggs and oocysts in feces. Fecal calprotectin and IgA concentrations were quantified by in‐house radioimmunoassays. Results: For each marker (IgA and calprotectin), a strong positive correlation was observed between concentration in fresh feces and concentration in fecal dry matter. 75.6% of the puppies were found to be infected by at ≥1 of the enteropathogens evaluated. Fecal calprotectin concentration was significantly influenced by age ( P = .001), with higher concentrations in younger puppies, but not by viral ( P = .863) or parasitic infection ( P = .791). Fecal IgA concentration was significantly influenced by enteropathogen shedding ( P = .01), with a lower fecal IgA concentration in puppies shedding at ≥1 enteropathogen compared to puppies without any enteropathogen shedding, but not by age. Conclusions: Fecal calprotectin and IgA are of no diagnostic value to detect presence of enteropathogens in clinically healthy puppies or puppies with abnormal feces, but could help to better understand the maturation of digestive tract.